Protective Properties of FOXO1 Inhibition in a Murine Model of Non-alcoholic Fatty Liver Disease Are Associated With Attenuation of ER Stress and Necroptosis - Ding, Hao-ran; Tang, Zhen-ting; Tang, Ning; Zhu, Zheng-yi; Liu, Han-yi; Pan, Chen-yan; Hu, An-yin; Lin, Yun-zhen; Gou, Peng; Yuan, Xian-wen; Cai, Jia-hui; Dong, Chun-long; et al. (Frontiers in Physiology, 2020)
Aims: The pathogenesis of nonalcoholic fatty liver disease is currently unclear, however, lipid accumulation leading to endoplasmic reticulum stress appears to be pivotal in the process. At present, FOXO1 is known to be involved in NAFLD progression. The relationship between necroptosis and non-alcoholic steatohepatitis has been of great research interest more recently. However, whether FOXO1 regulates ER stress and necroptosis in mice fed with a high fat diet is not clear. Therefore, in this study we analysed the relationship between non-alcoholic steatohepatitis, ER stress and necroptosis. Main methods: Male C57BL/6J mice were fed with an HFD for 14 weeks to induce non-alcoholic steatohepatitis. ER stress and activation of necroptosis in AML12 cells were evaluated after inhibition of FOXO1 in AML12 cells. In addition, mice were fed with AS1842856 for 14 weeks. Liver function and lipid accumulation were measured, and further, ER stress and necroptosis were evaluated by Western Blot and Transmission Electron Microscopy. Key findings: Mice fed with a high fat diet showed high levels of FOXO1, accompanying activation of endoplasmic reticulum stress and necroptosis. Further, sustained PA stimulation caused ER stress and necroptosis in AML12 cells. At the same time, protein levels of FOXO1 increased significantly. Inhibition of FOXO1 with AS1842856 alleviated ER stress and necroptosis. Additionally, treatment of mice with a FOXO1 inhibitor ameliorated liver function after they were fed with a high fat diet, displaying better liver condition and lighter necroptosis. Significance: Inhibition of FOXO1 attenuates ER stress and necroptosis in a mouse model of non-alcoholic steatohepatitis. Key words: non-alcoholic steatohepatitis, FOXO1, endoplasmic reticulum stress, necroptosis.